Unattended but not undernourished: young children left behind in rural China - de Brauw, Alan; Mu, Ren (International Food Policy Research Institute, 2012)
The unprecedented, large-scale, rural-to-urban migration in China has left many rural children living apart from their parents. Yet the consequences for child development of living without one or more parents due to migration are largely unknown. In this study, we examine the impact of parental migration on one measure of child development, the nutritional status of young children in rural areas. We use the interaction terms of wage growth in provincial capital cities with initial village migrant networks as instrumental variables to account for migration selection. Our results show that parental migration has no significant impact on the height of children but that it improves their weight. We provide suggestive evidence that the improvement in weight may be achieved through increased access to tap water in households with migrants. To conclude the paper, we raise concerns about the sustainability of the impact.